Pelatihan Pemasaran Produk Dimasa Pandemi Covid 19 Berbasis Social Media Pada UMKM Tahu Bakso Berkah Wijaya Di Batur Sari, Mranggen, Demak, Jawa Tengah - Firdaus Firdaus; Muhamad Roby Jatmiko; Wa Ode Sitti Nurrahmah (Society : Jurnal Pengabdian Masyarakat, 2022)
SME’s are one of the bases for supporting the economy of a country that deserves to be empowered. However, in its implementation it is not easy to require cooperation between various elements including the government, the community, and the role of universities. In this community service activity, the collaboration partner, the SME’s Tahu Bakso Berkah Wijaya, is located at jl. Batur sari, mranggen. Along the way, Wijaya's Bakso Blessings experienced various conventional marketing problems, because the owner was not familiar with technology as it is today. The purpose of this service is to teach MSME owners so that in marketing products, not only in the conventional way, but also by using this sata technology development by selling through social media. The method used in this case is in the form of sharing and providing training materials in the form of how to create an online store, how to sell on social media and how to become partners in existing start-up platforms. The results obtained from this service are the establishment of official social media accounts and packaging labels for MSME Tahu Bakso Berkah Wijaya which consists of FB, IG, and start-up partner accounts, namely Gojek and Grab. This also makes these SMEs more existent and easy to find for culinary lovers to know meatballs.